Long-term exposure to wood-preserving chemicals containing pentachlorophenol and lindane is related to neurobehavioral performance in women - Peper, Martin; Ertl, Michael; Gerhard, Ingrid (American journal of industrial medicine, 1999)
The adverse neurobehavioral effects of long-term low exposure to wood-preserving chemicals (WPC) containing solvents, pentachlorophenol (PCP) and γ-hexachlorocyclohexane (γ-HCH; lindane), and other neurotoxicants were investigated in a neuropsychological group study.